Optimization Instagram Content as @gokampusofficial Brand Communication Medium - Gloria Violita Manurung; Rewindinar Rewindinar; Rustono Farady Marta (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
Instagram is one of the popular social media companies used as a medium for brand communication. Instagram has a role in reaching the company's target audience more widely and unlimitedly. One company which uses Instagram as a medium in the brand communication strategy is GoKampus. GoKampus is a new application-based company where the target audience is the majority of Instagram users. This research was conducted to discover how GoKampus optimizes Instagram in the form of video content created as an effort to introduce their brand to Instagram users who are their target audiences. This study uses a qualitative content analysis method by analyzing the content on four series of videos on the @gokampusofficial Instagram account. The study focuses on four categories of video content, specifically 1) message content explaining the Instant Approval feature, 2) message content explaining the GoKampus brand identity, 3) written captions, and 4) the number of viewers and comments. The results show that the series of video content having been created was able to create brand awareness of the GoKampus; however, it was not optimal enough in building brand engagement from its followers. Therefore, this can be examined from the small number of comments and the number of viewers.